Exploring Experiences of Delayed Prescribing and Symptomatic Treatment for Urinary Tract Infections among General Practitioners and Patients in Ambulatory Care: A Qualitative Study - Sinead Duane; Paula Beatty; Andrew W. Murphy; Akke Vellinga (MDPI AG, 2016)
"Delayed or back up" antibiotic prescriptions and "symptomatic" treatment may help to reduce inappropriate antibiotic prescribing for Urinary Tract Infections (UTI) in the future. However, more research needs to be conducted in this area before these strategies can be readily promoted in practice. This study explores General Practitioner (GP) and patient attitudes and experiences regarding the use of delayed or back-up antibiotic and symptomatic treatment for UTI. Qualitative face to face interviews with General Practitioners (n = 7) from one urban and one rural practice and telephone interviews with UTI patients (n = 14) from a rural practice were undertaken. Interviews were analysed using framework analysis. GPs believe that antibiotics are necessary when treating UTI. There was little consensus amongst GPs regarding the role of delayed prescribing or symptomatic treatment for UTI. Delayed prescribing may be considered for patients with low grade symptoms and a negative dipstick test. Patients had limited experience of delayed prescribing for UTI. Half indicated they would be satisfied with a delayed prescription the other half would question it. A fear of missing a serious illness was a significant barrier to symptomatic treatment for both GP and patient. The findings of this research provide insight into antibiotic prescribing practices in general practice. It also highlights the need for further empirical research into the effectiveness of alternative treatment strategies such as symptomatic treatment of UTI before such strategies can be readily adopted in practice.